(untitled) (UNWE Yearbook, 2009)
The scientific study represents a synthesis and the outcome of more than three decades of the author’s experience in macroeconomic forecasting and modeling. Each management needs assessing the immediate outlook, outlining the future developments with a view to overcoming possible negative implications as well as making the best out of any propitious turn of the situation. These processes become highly complicated at a macroeconomic level when the macroeconomic managerial elite is supposed to take into account and comply with the preferences of a dominant part of society. The clash of interests has to find an expression in something in-between which as a rule resorts to the art of making social compromises.The study is divided into eight chapters, with an introduction and conclusion. Various aspects of social and economic life are being discussed and analyzed in succession. They presume and require taking into consideration the respective specificity in attempting to forecast the look forward. A special attention is paid to characterizing the so called paradox of economic thinking which should bear in mind the historic development of processes and simultaneously draw the outlines of a future which is theoretically impossible to know. The possibilities for applying mathematical applications in modeling macroeconomic processes are analyzed with an emphasis on their content limitations. The macroeconomic optimum is subjected to criticism as well as the attempts at enforcing a kind of programmed future. The principle lies in the presumption in the theory of public choice, which examines the representatives of macroeconomic management as individuals free from the halo of idealization, supposedly seeking the pure public good only. There is also a critical discussion of the concept of social market economy, which in the real experience of the transition to market economy was loaded with too much of ideological content.The author makes an attempt at systematizing and analyzing the views of eminent economists and scientists on the international arena and Bulgaria. The idea is to work out some methodology which should lie in the basis of forecasting macroeconomic proportions.